Trends of teenage pregnancy in Brazil, 2000-2011 - Vaz,Raquel Ferreira (2016)
Summary Objective: To evaluate the frequency of teenage pregnancy in Brazil, from 2000 to 2011, in all five Brazilian macroregions and age groups (10-14 and 15-19 years), correlating it with the human development index (HDI). Method: Descriptive epidemiological study, with cross-sectional design, performed by searching the database of the National Health System (Datasus), using information from the Information System (Sinasc). Results: There was a decrease in the percentage of live births (LB) from teenage mothers (10-19 years) in Brazil (23.5 % in 2000 to 19.2 % in 2011). This reduction was observed in all Brazilian macroregions in the group of mothers aged 15 to 19 years. The number of LB increased by 5.0% among mothers aged 10-14 years (increase in the North and Northeast and decline in the other macroregions). The proportion of LB shows an inversely proportional trend to HDI score, with the Southeast having the highest HDI and the lowest proportion of LB to teenage mothers in the country. Conclusion: Brazil shows a decline in the percentage of LB to adolescent mothers, tending to be inversely related to HDI score. It is important to empower strategies to address the problem, so that teenage pregnancy is seen as a personal decision rather than the result of a lack of policies targeting adolescent health.